The Five Eyes of the Devil: corporal punishment in nineteenth century schools - Daniel Cavalcanti de albuquerque Lemos (Universidade Federal do Rio Grande do Sul, 2012)
This study examines the practice of corporal punishment in primary schools of the court, investigating it as a form of discipline, establish and consolidate a particular school culture, here understood as a set of norms, attitudes and behaviors imposed on young people as a way to obtain a disciplining of body and spirit. The Paddling, was an object that just as the book, table, pen, marked their presence at school and in the imagination of society about the school. The point of being portrayed in the literature of the time. Analyze sources that demonstrate the course of discussion of punishment, the limits of authority of the teacher and the intervention of society inthis debate.